Differential distribution of aggrecan isoforms in perineuronal nets of the human cerebral cortex - Virgintino, Daniela (J Cell Mol Med, 2009)
Aggrecan is a component of the CNS extracellular matrix (ECM) and we show here that the three primary alternative spliced transcripts of the aggrecan gene found in cartilage are also present in the adult CNS. Using a unique panel of core protein-directed antibodies against human aggrecan we further show that different aggrecan isoforms are deposited in perineuronal nets (PNNs) and neuropil ECM of Brodmann’s area 6 of the human adult cerebral cortex. According to their distribution pattern, the identified cortical aggrecan isoforms were subdivided into five clusters spanning from cluster 1, comprised isoforms that appeared widespread throughout the cortex, to cluster 5, which was an aggrecan-free subset. Comparison of brain and cartilage tissues showed a different relative abundance of aggrecan isoforms, with cartilage-specific isoforms characterizing cluster 5, and PNN-associated isoforms lacking keratan sulphate chains. In the brain, isoforms of cluster 1 were disclosed in PNNs surrounding small-medium interneurons of layers II–V, small-medium pyramidal neurons of layers III and V and large interneurons of layer VI. Aggrecan PNNs enveloped both neuron bodies and neuronal processes, encompassing pre-terminal nerve fibres, synaptic boutons and terminal processes of glial cells and aggrecan was also observed in continuous ‘coats’ associated with satellite, neuron-associated cells of a putative glial nature. Immunolabelling for calcium-binding proteins and glutamate demonstrated that aggrecan PNNs were linked to defined subsets of cortical interneurons and pyramidal cells. We suggest that in the human cerebral cortex, discrete, layer-specific PNNs are assembled through the participation of selected aggrecan isoforms that characterize defined subsets of cortical neurons.